A vitamin C fuel cell with a non-bonded cathodic interface. Issue 8 (29th June 2018) - Devendrachari, Mruthyunjayachari Chattanahalli; Thimmappa, Ravikumar; Bhat, Zahid Manzoor; Shafi, Shahid Pottachola; Nimbegondi Kotresh, Harish Makri; Kottaichamy, Alagar Raja; Venugopala Reddy, Kallam Ramareddy; Thotiyl, Musthafa Ottakam
Abstract : Precious metal free hybrid vitamin C fuel cell redox flow battery. Abstract : Vitamin C is a naturally occurring molecule with antioxidant properties, and it often plays a pivotal role in many chemical and biochemical processes. We show that a cobalt-based molecular electrocatalyst can mediate the electron donation from vitamin C which upon coupling with a non-bonded and reversible electron acceptor; the electron flow between the half cells can be channeled in a precious-metal-free configuration. The non-bonded nature of the electron acceptor allows fast interfacial kinetics even on simple carbon particles and arrests the cathode-derived parasitic chemistry often encountered in oxygen breathing fuel cells. Consequently, a vitamin C fuel cell driven by the non-bonded cathodic interface demonstrates ∼18 times higher performance metrics compared to the precious-metal-based vitamin C–O2 configuration. Due to the renewable nature of the fuel and the precious metal-free configuration in the proposed non-bonded architecture, the cell can noticeably reduce the cost of electricity per kW with potential practical applications in powering commercial electrical appliances.